Fausto Felipe Rodríguez, one of the pioneers of Cuban maxillofacial surgery - Denia Morales Navarro; Carlos Manuel Cruañas Sospedra; Josefa Dolores Miranda Tarragó (Editorial Ciencias Médicas, 2019)
...........